Uji Kinerja Surface Scanner 3D Menggunakan Sensor VL53L0X dan Mikrokontroler ATMEGA8535 - Maria, Putut Son; Susianti, Elva (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2019)
Digital data recording of the geometry of 3-dimensional objects require a 3D scanner tool which are mostlyÃ‚Â using an imagery sensor. However there is hardly used information of scanned result, named color. Imagery sensorÃ‚Â requires high spesification processing unit as capable as a personal computer for data acquisition processing. ThisÃ‚Â research aims to build a 3D surface scanner using a time of flight laser ranging sensor and to develop its simpleÃ‚Â function to become more valuable device. Using point to point displacement method, the sensor measures the distanceÃ‚Â between the outermost point of the object and the sensor surface perpendicularly, once when one measurement isÃ‚Â done then the object to be rotated along with the rotary table. The prototype was built using the VL53L0X sensor andÃ‚Â ATMEGA8535 microcontroller as a motor controller for rotary table and vertical axis. Scanned data is sent from theÃ‚Â microcontroller to the computer to be visualized in real time. The results show that the VL53L0X sensor is suitable forÃ‚Â scanning convex objects but it is not capable to handle objects with multiple cavities.